Molar‐incisor malformation: Eight new cases and a review of the literature. Issue 2 (14th November 2019) - Vargo, Richard J.; Reddy, Rekha; Da Costa, Walmir B.; Mugayar, Leda R.F.; Islam, Mohammed N.; Potluri, Anitha
Abstract: Background: Molar‐incisor malformation (MIM) is a recently described dental abnormality. While MIM mimics dentin dysplasia, it presents in a localized pattern. Furthermore, it is speculated that MIM is caused by significant early‐life medical history. Aim: The purpose of this study is to present a series of MIM cases and compare the findings with the literature. Design: An extensive search of all published cases of MIM in the English‐language literature was conducted. Additionally, an institutional review board‐approved retrospective search was performed within the University of Florida oral pathology biopsy service archives. Radiographic consultation cases were also included. Cases lacking radiographs were excluded. Results: Seventy‐nine cases were identified in the literature, and eight cases were identified in our retrospective search. All but one case involved the permanent first molars. The average age at diagnosis was 9 years. Many patients reported significant early‐life medical histories. Conclusions: MIM usually affects the permanent first molars and may be linked to early‐life medical conditions or interventions. Oral healthcare providers, especially paediatric dentists, should be aware of MIM to avoid misdiagnosing it as dentin dysplasia. Long‐term follow‐up studies with thorough medical history documentation are essential to understand the pathogenesis and aetiology and to create treatment guidelines.